x²-2x-1²+x²+2*x*2+2²-x²-2²=24
x²-2x-1+x²+4x+4-x²-4=24(+x² cu -x² se reduc si da 0)(+4 cu -4 se reduc si da 0)
x²-2x+4x-1-24=0
x²+2x-25=0
Δ=b²-4ac
=2²-4*1*(-25)
=4+100
104
x₁,x₂=[tex] \frac{-b+- \sqrt{D} }{2a} [/tex]
=-2+-√104supra 2
x1=-2-√104 supra 2
x2=-2+√104 supra 2
b)
x²-2*x*2-2²+x²+2x+1²-x²+1²=14
x²-4x-4+x²+2x+1-x²+1=14(+x² cu -x² se reduc si da 0 )
x²-4x+2x+1+1-14=0
x²-2x-12=0
Δ=b²-4ac
=(-2)²-4*1(-12)
=4+48
=32
x1,x1=-b+-(aici trebuie sa vine unul sub altul)√32supra 2
x1=-(2)+√32supra2
=2+√32 supra 2
x2=-(-2)-√32 supra 2
=2-√32 supra 2